إعادة تأهيل سوق الأقواس حد الصحاري بالجلفة: التشخيص و الأشغال الاستعجالية - براهيمي, فاطمة الزهراء; Takhi, Belkacem, Directeur de thèse; Belhadj, Belkacem, Directeur de thèse (My University, 2022)
The markets represent an important role in the ancient architectural heritage and the formation of its first nucleus, as well as the revival of the regional commercial activity of the region and the contribution to commercial exchanges and to civil architecture in particular to any civilization on the face of history due to its architectural, historical and social value that generations passed down through the ages, but it is an extension of civilizations that preceded the Islamic civilization, where It was among the foundations of the formation and formation of ancient cities. Our study in the master dealt with the idea of re-employing the arches market from a technical point of view, diagnosis and urgent works, as the arches market is one of the oldest landmarks in the region, the limit of deserts and its current status in the case of a landmark threatened with collapse and deteriorating. For the safety of visitors to this historical monument. As for the jobs that he went through history, they lack documentation, up to the property of Sheikh Al-Zawiya, Ain Aghlal, which used it as an Islamic endowment and Quran memorization center, and recently a shelter for the poor and needy before it was closed by the Directorate of Culture. It is positively reflected on the surrounding area and on HAD SHARY and Djelfa as well
Laghouat : Université Amar Telidji - Département d'architecture Option : Architecture et patrimoine